PENGARUH LITERASI DAN NUMERASI DALAM MENINGKATKAN HASIL ASESEMEN KOMPETENSI MINIMUM KELAS 5 SDN GADING KULON II KABUPATEN PROBOLINGGO TAHUN PELAJARAN 2022/2023 - Mentari Putri, Laura Marsya; Aini, Ika Nur; Fitriyana, Fitriyana; Sriwijayanti, Ribut Prastiwi (Prodi PGMI STIT Sunan Giri Bima, 2022)
Literacy and Numeracy will be the main components in the Minimum Competency Assessment (AKM) as a substitute for the National Examination. This minimal ability consists of the ability or quality of literacy in a person in which there is the ability to read, write, and also recognize and understand ideas visually (literacy), the ability to apply number concepts and arithmetic skills in everyday life and interpret quantitative information that is around us, this ability is evidenced by a sense of comfort with numbers and cleverness in applying mathematical skills (numeration). The data was collected by the researchers directly from SDN Gading Kulon II Probolinggo Regency, including: a) Class AKM Pretest, which is a test before implementing literacy and numeracy that provides questions obtained from the Motivation application provided by the Ministry of Education and Culture. (b) Observation, how to collect data by direct observation of learning activities in class on the object to be studied. (c) Documentation of how to collect data includes archives, archives and photos related to the problem under study. (d) Posttest AKM Class, contains questions regarding literacy and numeracy which are also obtained from the Motivation application provided by the Ministry of Education and Culture. The results showed that the scores obtained by students increased after the implementation of literacy and numeracy. The data obtained in table 2 shows a significant increase compared to table 1 data. The percentage of success in table 2 is for literacy 95% to achieve completeness and for numeration 89% to achieve completeness.